Imbricando projetos de ensino-aprendizagem e tecnologias digitais de rede : busca de re-significações e potencialidades - Malaggi, Vitor (2009)
The study presented in this dissertation aims to find answers, based on a set of theoretical ponderations and practical activities, to the problem of the appropriation of the Digital Network Technologies (DNTs) and its features as means to the potentialization of the educational fundaments of the Teaching-Learning Projects (TLPs), didactic systems that take the Projects on education as new meanings. Thus, a bibliographic review was initially made, taking as main goal the construction of a theoretical basis and the concept definitions on these two issues. From this study, it was possible to draw the proposition of interdisciplinary union between the theoretical points of the DNTs and TLPs, generating, as a result, three conceptual axis of intersection. With this work, a methodological purpose for ethnographic type research was made, taking as target the students from the 2nd and 4th grades from the State Elementary School Capistrano de Abreu. After the investigation process, analysis procedures were performed that made possible the revealing of the data obtained during the empirical research, helping in the interpretation of the possibilities opened with the approach to the DNTs in an educational environment, based on the assumptions of the TLPs. Through this analytical process, it was concluded that the intrinsic characteristics of these technologies are capable of potentializing the DNTs, assuming the teaching-learning processes as based on the perspective of collaboration/cooperation, on the receptiveness for new relationships and on the redefinition of the roles of teachers and students, as well as on the reorganization of the subjects table and the time-space of learning-teaching